"It is a process" - a qualitative evaluation of provider acceptability of HIV assisted partner services in western Kenya: experiences, challenges, and facilitators - Wenjia Liu; Beatrice M. Wamuti; Mercy Owuor; Harison Lagat; Edward Kariithi; Christopher Obong'o; Mary Mugambi; Monisha Sharma; Rose Bosire; Sarah Masyuko; David A. Katz; Carey Farquhar; et al. (BMC, 2022)
Abstract Background Assisted partner service (APS) is effective for increasing HIV testing services (HTS) uptake among sexual partners of people diagnosed with HIV with rare social harm. The acceptability of APS to HTS providers is important for the quality and effectiveness of APS delivery. Within a larger ongoing implementation science study of APS in western Kenya, we qualitatively evaluated the provider acceptability of APS. Methods From May-June 2020, we conducted virtual, semi-structured in-depth interviews with 14 HTS providers recruited from 8 of 31 study health facilities in Homa Bay and Kisumu counties. Participants were selected using criteria-based purposive sampling to maximize variation on patient volume (assessed by the number of index clients tested for HIV) and APS performance (assessed by sexual partners elicitation and enrollment). Interviews inquired providers' experiences providing APS including challenges and facilitators and the impact of contextual factors. Data were analyzed using an inductive approach. Results Overall, HTS providers found APS acceptable. It was consistently reported that doing APS was a continuous process rather than a one-day job, which required building rapport and persistent efforts. Benefits of APS including efficiency in HIV case finding, expanded testing coverage in men, and increased HIV status awareness and linkage to care motivated the providers. Provider referral was perceived advantageous in terms of independent contact with partners on behalf of index clients and efficiency in partner tracing. Challenges of providing APS included protecting clients' confidentiality, difficulty obtaining partners' accurate contact information, logistic barriers of tracing, and clients' refusal due to fear of being judged for multiple sexual partners, fear of breach of confidentiality, and HIV stigma. Building rapport with clients, communicating with patience and nonjudgmental attitude and assuring confidentiality were examples of facilitators. Working in rural areas and bigger facilities, training, supportive supervision, and community awareness of APS promoted APS delivery while low salaries, lack of equipment, and high workload undermined it. Conclusions HTS providers found APS acceptable. Delivering APS as a process was the key to success. Future scale-up of APS could consider encouraging provider referral instead of the other APS methods to improve efficiency and reduce potential harm to clients.